REVIEW OF CHARACTERISTIC FEATURES OF ABHRAKA WSR TO PINAKA ABHRAKA - GUPTA, JAY PRAKASH; GOYAL, MANISHA; AGARWAL, RAJARAM (Innovare Journal of Ayurvedic Sciences, 2021)
Rasashastra (Vedic chemistry) is the root branch of the Ayurveda (the science of life) that deals with herbomineral preparations. Abhraka (mica) is a mineral that classified in Maharasa group of Rasashastra. It contains several elements such as Si, Fe, Al, Mg, Na, and K as main ingredients. Four types of abhrakas are described in the Classics of Rasashastra including pinaka. Property of Pinaka is told that when it is heated on fire, the layers get separates. Intake of its bhasma causes severe constipation. The characteristic effect of pinak abhraka can be correlated with muscovite – paragonite micas. Because their perfect basal cleavage allows them to be split into thin, flexible sheets. Muscovite–paragonite series group of mica having hydrous potassium, sodium, aluminum, and silicate minerals. In this hydrous group, aluminum hydroxide causes constipation. In this paper, an attempt will be made to explain how does pinaka abhrak causes severe constipation.